The problem of negatives generated by the commodity technology model in input-output analysis: A review of the solutions - Thijs ten Raa; José Rueda-Cantuche (Journal of Economic Structures, 2013)
Many economic models (e.g., computable general equilibrium models, econometric input-output models) revolve around a matrix of technical coefficients. However, these matrices can be estimated only once every 5 years as long as they are calculated from input-output tables and these are only published on a 5-year basis. Alternatively, use and make (or supply) tables are being regularly published on a yearly basis. However, they need to be converted into input-output tables as a previous step to form the matrix of technical coefficients. In doing so, this paper aims to shed light on the construction process of input-output tables and to guide economic modelers in making a decision on the way to make such conversion and how to deal with the subsequent problems, particularly with negative technical coefficients.
Keywords: C67; D57; 330; input-output analysis; technical coefficients; use and make tables; input-output modeling; Input-Output-Analyse; Modellierung; Lineare Algebra; Theorie